Analysis Of Perceveid Seriousness With Covid-19 Prevention Practice Among Urban Community In Kediri City - Yudhana, Amarin; Mayasari, Ema; Bastian, Ardi (Universitas STRADA Indonesia, 2021)
background:Corona disease (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus. Almost all over the world the number of COVID-19 cases continues to show an increase in the number of cases. Towards the end of 2021 in Indonesia, there are still additional cases of covid 19 which currently reaches 4,244,761. Meanwhile, the Covid-19 case that occurred in Kediri City is still adding new confirmations every day, although not as much as in the previous period. The addition was also accompanied by the addition of recovered patients. In this case, the application of health protocols is very necessary in preventing the spread of covid 19. So the purpose of this study is to analyze the perception of seriousness in preventing covid 19 disease in urban communities in Kediri City. Method : The research design used is analytic with a cross-sectional approach. The sample amounted to 144 spread over 3 sub-districts in the city of Kediri which was taken by simple random sampling. The data was processed using the Pearson Correlation test to see the relationship between perceived seriousness and covid 19 prevention practices. Result: Of the 144 respondents, some of them felt that COVID-19 was a serious disease and most of their behavior had implemented health protocols, although there were still people who did not implement health protocols in their daily activities. The significance value of the Pearson Correlation test: 0.000 < 0.05 there is a relationship between perceived seriousness and covid 19 prevention practices. Pearson correlation value: 0.761 means that perceived seriousness is positively related to covid 19 prevention practices and has a strong degree of correlation